Comparing and Optimization of Material Removal Rate of Cryogenically Treated and Untreated Copper Tools Using EDM - Virdi, Roshan Lal; Chawla, Prince; Singh, Supinderjit (Asian Journal of Engineering and Applied Technology, 2016)
Super alloys are advanced engineering materials, having high potential for aerospace and defence industries. Inconel 625, a nickel-chromium heat resistant alloy, finds its applications in the manufacturing of aerospace fasteners, gas turbine engineering and heat treatment equipment. In this study, electric discharge machining is used for making holes on inconel 625. Three control factors namely pulse current, pulse on time and flushing pressure having three levels each be taken into consideration and material removal rate (MRR) was taken as a response measure. Experiments were based on (L18 21×33) orthogonal array of Taguchi’s methodology. Results analyzed showed that MRR increased as pulse current and tool electrode rotation increased. MRR was more for tool electrodes cryogenically treated than tool electrodes untreated.